1993
DOI: 10.1103/physrevlett.71.440
|View full text |Cite
|
Sign up to set email alerts
|

NMR study of local structure in metallicLa2CuO4+δ

Abstract: We employ l39 La NMR spectroscopy as a structural probe of metallic La2Cu04+a. We find a distribution of lateral displacements of the oxygen atoms which form the apices of the oxygen octahedra. We directly observe a wide distribution of structures of the La-O layer; this distribution is strongly temperature dependent. We present copper NQR spectra which reveal a second, unexplained, copper site in the Cu02 planes. We show that these features are not manifestations of disturbances of the lattice by interstitial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
38
1

Year Published

1994
1994
2012
2012

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(43 citation statements)
references
References 15 publications
4
38
1
Order By: Relevance
“…2 indicates the unique value of the EFG in the system, the two 139 La peaks are attributed to the local tilting of the direction of the EFG at the 139 La with respect to the c axis, 22 where θ m corresponds to the angle at which the direction of the EFG is parallel to H.…”
Section: Figmentioning
confidence: 99%
“…2 indicates the unique value of the EFG in the system, the two 139 La peaks are attributed to the local tilting of the direction of the EFG at the 139 La with respect to the c axis, 22 where θ m corresponds to the angle at which the direction of the EFG is parallel to H.…”
Section: Figmentioning
confidence: 99%
“…Thus, by studying La NMR, Hammel, et al [547] have found that in La 2 CuO 4+δ there is not a single, well-defined octahedral tilt angle in the LTO phase, but rather an extremely broad distribution, from essentially zero tilt up to some maximum value, Fig. 54.…”
Section: B Short-range Order and The Dynamical Jt Phasementioning
confidence: 99%
“…54 [547]: while the superconducting phase has a broad distribution of tilt angles, the AFI phase has a well-defined LTO tilt (the splitting of the AFI peaks is due to the magnetic field). Hence the AFI appears to be correlated with a static LTO phase, like the solitons in Fig.…”
Section: Relation To Dynamic Jt Effectmentioning
confidence: 99%
“…While these domains are regularly found in STM studies when the samples are cleaved at low-temperature, they can be annealed out at high temperatures 35 . This could be caused by a 'melting' of the EPS, as is found in LCO near room temperature 36 , and can be tested by careful annealing studies. Alternatively, it may be a question of pinning the EPS.…”
Section: Domain Phasementioning
confidence: 99%